Interventions for smoking cessation in hospitalised patients: a systematic review. Issue 8 (1st August 2001) - Munafò, M; Rigotti, N; Lancaster, T; Stead, L; Murphy, M
Abstract : BACKGROUND: An admission to hospital provides an opportunity to help people stop smoking. Individuals may be more open to help at a time of perceived vulnerability, and may find it easier to quit in an environment where smoking is restricted or prohibited. Providing smoking cessation services during hospitalisation may help more people to attempt and sustain an attempt to quit. The purpose of this paper is to systematically review the effectiveness of interventions for smoking cessation in hospitalised patients. METHODS: We searched the Cochrane Tobacco Addiction Group register, CINAHL, and the Smoking and Health database for studies of interventions for smoking cessation in hospitalised patients. Randomised and quasi-randomised trials of behavioural, pharmacological, or multi-component interventions to help patients stop smoking conducted with hospitalised patients who were current smokers or recent quitters were included. Studies of patients admitted for psychiatric disorders or substance abuse, those that did not report abstinence rates, and those with follow up of less than 6 months were excluded. Two of the authors extracted data independently for each paper, with assistance from others. RESULTS: Intensive intervention (inpatient contact plus follow up for at least 1 month) was associated with a significantly higher cessation rate compared with controls (Peto odds ratio (OR) 1.82, 95% CI 1.49 to 2.22). Any contact during hospitalisation followed by minimal follow up failed to detect a statistically significant effect on cessation rate, but did not rule out a 30% increase in smoking cessation (Peto OR 1.09, 95% CI 0.91 to 1.31). There was insufficient evidence to judge the effect of interventions delivered only during the hospital stay. Although the interventions increased quit rates irrespective of whether nicotine replacement therapy (NRT) was used, the results for NRT were compatible with other data indicating that it increases quit rates. There was no strong evidence that clinical diagnosis affected the likelihood of quitting. CONCLUSIONS: High intensity behavioural interventions that include at least 1 month of follow up contact are effective in promoting smoking cessation in hospitalised patients.